The use of non-destructive tests to estimate Self-compacting concrete compressive strength - Djamila Boukhelkhal; Mohamed Guendouz (MATEC Web of Conferences, 2018)
Until now, there are few studies on the effect of mineral admixtures on correlation between compressive strength and ultrasonic pulse velocity for concrete. The aim of this work is to study the effect of mineral admixture available in Algeria such as limestone powder, granulated slag and natural pozzolana on the correlation between compressive strength and corresponding ultrasonic pulse velocity for self-compacting concrete (SCC). Compressive strength and ultrasonic pulse velocity (UPV) were determined for four different SCC (with and without mineral admixture) at the 3, 7, 28 and 90 day curing period. The results of this study showed that it is possible to develop a good correlation relationship between the compressive strength and the corresponding ultrasonic pulse velocity for all SCC studied in this research and all the relationships had exponential form. However, constants were different for each mineral admixture type; where, the best correlation was found in the case of SCC with granulated slag (R2 = 0.85). Unlike the SCC with pozzolana, which have the lowest correlation coefficient (R2 = 0.69).